The alpha-Tomatine Exhibits Antiproliferative Activity, Rupture of Cell Membranes and Induces the Expression of APC Gene in the Human Colorectal Adenocarcinoma Cell Line (Ht-29) - Ishii, Priscila Lumi [UNESP]; Oliveira, Rodrigo Juliano; Mauro, Mariana de Oliveira [UNESP]; Zorgetto-Pinheiro, Veronica Assalin; Sartori, Daniele; Lepri, Sandra Regina; Baranoski, Adrivanio; Mantovani, Mario Sergio; Ribeiro, Lucia Regina [UNESP] (Inst Tecnologia Parana, 2020)
The alpha-tomatine is a steroidal glycoalkaloid found in immature tomatoes (Lycopersicon esculentum) that has important biological functions including the inhibition of cancer cell growth and preventing metastasis. This study aimed to evaluate the effects of alpha-tomatine on cytotoxicity, cellular proliferation, apoptosis, and mRNA expression of APC, CCNA2, beta-catenin, CASP9, BAK, BAX and BCL-XL in colorectal adenocarcinoma cell line HT-29. HT29 cells were treated with three concentrations of alpha-tomatine (0.1, 1 and 10 mu g/mL), although only the 1 mu g/mL concentration of alpha-tomatine was used to evaluate genetic expression patterns by real time-PCR. Results showed that alpha-tomatine was cytotoxic only at the 10 mu g/mL concentration. Cell proliferation was significantly inhibited after the first 24 hours of treatment only with concentrations of 10 mu g/mL. In contrast, there were no significant differences in apoptosis for any treatment. In the gene expression studies, only APC expression was significantly altered by alpha-tomatine treatment. In conclusion, tomatine has antiproliferative activity in the first 24h of treatment, does not induce apoptosis in this cell line and causes disruption of cell membranes, thereby increasing the expression of APC gene related to cell cycle.
Keywords: alpha-tomatine; gene expression; cytotoxicity; cell cycle; DNA damage